2022
DOI: 10.1021/acsami.2c10088
|View full text |Cite
|
Sign up to set email alerts
|

Processable Conjugated Microporous Polymer Gels and Monoliths: Fundamentals and Versatile Applications

Abstract: Conjugated microporous polymers (CMPs) as a new type of conjugated polymers have attracted extensive attention in academia and industry because of the combination of microporous structure and π-electron conjugated structure. The construction and application of gels and monoliths based on CMPs constitute a fertile area of research, promising to provide solutions to complex environmental and energy issues. This review summarizes and objectively analyzes the latest advances in the construction and application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…The field of porous materials has expanded since the beginning of this century from traditional inorganic materials to crystalline covalent organic frameworks (COFs). The design and synthesis of porous materials is a frontier field of research due to their wide range of applications, including gas capture and separation, water treatment, , energy storage, and heterogeneous catalysis. Based on the degree of long-range structural ordering, porous materials can be classified as amorphous and crystalline. Hyper-cross-linked polymers (HCPs), polymers of intrinsic microporosity (PIMs), , and conjugated microporous polymers (CMPs) , are classified as amorphous, whereas zeolites, , MOFs, porous molecular cages, , and COFs fall into the class of porous crystalline materials. Unlike traditional porous organic polymers (such as linear, branched, or cross-linked polymers), COFs exhibit long-range ordering, designable structures, and uniform and nanometer-scale pores .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of porous materials has expanded since the beginning of this century from traditional inorganic materials to crystalline covalent organic frameworks (COFs). The design and synthesis of porous materials is a frontier field of research due to their wide range of applications, including gas capture and separation, water treatment, , energy storage, and heterogeneous catalysis. Based on the degree of long-range structural ordering, porous materials can be classified as amorphous and crystalline. Hyper-cross-linked polymers (HCPs), polymers of intrinsic microporosity (PIMs), , and conjugated microporous polymers (CMPs) , are classified as amorphous, whereas zeolites, , MOFs, porous molecular cages, , and COFs fall into the class of porous crystalline materials. Unlike traditional porous organic polymers (such as linear, branched, or cross-linked polymers), COFs exhibit long-range ordering, designable structures, and uniform and nanometer-scale pores .…”
Section: Introductionmentioning
confidence: 99%
“…13−15 Based on the degree of long-range structural ordering, porous materials can be classified as amorphous and crystalline. Hyper-cross-linked polymers (HCPs), 16 polymers of intrinsic microporosity (PIMs), 17,18 and conjugated microporous polymers (CMPs) 19,20 are classified as amorphous, whereas zeolites, 21,22 MOFs, 23 porous molecular cages, 24,25 and COFs 26 fall into the class of porous crystalline materials. Unlike traditional porous organic polymers (such as linear, branched, or cross-linked polymers), COFs exhibit long-range ordering, designable structures, and uniform and nanometer-scale pores.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41] Even though CMPs have been employed in numerous elds, including photocatalysis, drug delivery, gas storage, gas separation, dye removal, and uorescence detection, their uses as SCs electrodes are restricted by their subpar conductivity, which signicantly decreases their capacitance. [42][43][44][45][46][47][48][49][50][51][52][53][54] CMPs are generally mixed with other conductive materials to boost the conductivity of CMP-based electrodes. Unfortunately, it is challenging to considerably improve the CMP performance due to the poor connection between the CMP and conductor.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, luminescence-based persistent luminescent (PersL) anti-counterfeiting materials have attracted widespread attention due to their easy implementation, good concealment, difficulty in replication, high emission intensity, multiple emission colors, long emission life, and applicability to mass production. [33][34][35][36][37] PersL materials have been widely studied and applied in the fields of special lighting, [38,39] light storage [40,41] and military engineering [42,43] because of their characteristics of continuous luminescence under dark conditions, however, the application in the field of dynamic anti-counterfeiting technology is rare. We have combined PersL materials and anti-counterfeiting applications and found that dynamic anticounterfeiting marking applications can be prepared.…”
Section: Introductionmentioning
confidence: 99%